Sexual abuse of children : a human rights perspective - Levesque, Roger J. R. (Bloomington : Indiana University Press, 1999)
This book considers how human rights law can help define what could and should be done to protect children from sexual maltreatment. The volume explores diverse forms of sexual maltreatment, compares societal responses to existing research and policies, uncovers basic themes, and proposes directions for future action. Roger Levesque places particular emphasis on the ways abusive activities in different countries and societies are linked with one another and the way diverse societal views of children place them at risk.
1. Invisible Acts: Child Sexual Maltreatment across World Cultures -- 2. Transforming Legal Conceptions of Childhood: The Global Human Rights Revolution -- 3. Deconstructing Childhood and Sexual Maltreatment -- 4. The Sexual Exploitation of Children -- 5. The Sexual Use of Children -- 6. Abuse by Adult Offenders -- 7. Abuse by Young Offenders -- 8. Reconstructing the Law of Childhood, Cultural Life, and Sexual Maltreatment.
Includes bibliographical references and index.
Keywords: Child sexual abuse; Children's rights